Simultaneous and alternate combinations of action-observation and motor imagery involve a common lower-level sensorimotor process. (November 2022) - Romano-Smith, S.; Roberts, J.W.; Wood, G.; Coyles, G.; Wakefield, C.J.
Abstract: Combining the motor simulation techniques of action observation and motor imagery (AOMI) is known to enhance motor performance more than when these techniques are presented in isolation. The present study examined the involvement of lower-level sensorimotor processes for the improvement in a dart-throwing task using AOMI. Novice participants (n = 70) were assessed on their dart-throwing both before and after a six-week AOMI training intervention that was contingent upon the random allocation of groups. Participants were randomly allocated into groups involving AOMI, where they observed either a congruent action, incongruent action or fixation cross (control), while simultaneously or alternately imagining the dart-throwing task. Dart-throwing performance was significantly more improved for the simultaneous- and alternate-congruent groups compared to the simultaneous-fixation and control groups. There was no indication of improvement by any of the other groups. This improvement appeared to coincide with lower EMG activity at the agonist and antagonist muscles, which would indicate greater movement efficiency. The findings suggest that AOMI involves a common lower-level sensorimotor process, which can lead to motor facilitation or interference, dependent upon whether the simulation techniques are congruent or incongruent with each other, respectively. What's more, this feature does not appear to differ as a function of the structure of delivery (i.e., simultaneous vs. alternate). Highlights: Examined the sensorimotor processes underlying motor performance by AOMI. Simultaneous and alternate AOMI equally enhance motor performance. Incongruent AO within simultaneous and alternate AOMI attenuates motor performance. AO and MI may utilise a common lower-level sensorimotor process. Fixation during AO disrupts motor improvements, which suggests a role for eye movements.